The role of the mosque and its relevance to social work. (May 2016) - Al-Krenawi, Alean
This article examines the significant role of the mosque in the Muslim community. In addition to being a place of prayer, the mosque provides educational, political welfare, and conflict resolution services in times of dispute between groups, families, couples, and individuals. Practitioners, social workers, psychologists, and psychiatrists from Western cultures lack the informal information that can provide a full understanding of the ways in which Muslims cope in times of crisis. We suggest that social workers should expand their knowledge of the mosque and the Imam and acknowledge the vital role they play in the Muslim community. We believe that the mosque and Imam can work together with the social workers and supply the cultural and social knowledge that is required for the proper assistance to be given. This approach will help bridge the gap between local-religious and Western models of intervention.